Organotin Compounds Toxicity: Focus on Kidney - Barbosa, Carolina Monteiro de Lemos; Ferrão, Fernanda Magalhães; Graceli, Jones B. (Frontiers in Endocrinology, 2018)
Organotin compounds (OTs) are synthetic persistent organometallic xenobiotics widely used in several commercial applications. They exert well-described harmful effects in brain, liver, adipose tissue and reproductive organs, as they are endocrine-disrupting chemicals (EDCs), but the effects in the kidneys are less known. The kidneys are especially vulnerable to environmental contaminants because they are a metabolizing site of xenobiotics, therefore, pollutants can accumulate in renal tissue, leading to impaired renal function and to several renal abnormalities. Individuals chronically exposed to OTs present a three-fold increase in the prevalence of kidney stones. These compounds can directly inhibit H+/K+-ATPase in renal intercalated cells, resulting in hypokalemia, renal tubular acidity and increased urinary pH, which is a known risk factor for kidney stones formation. OTs effects are not only limited to induce nephrolithiasis, its nephrotoxicity is also due to increased reactive oxygen species (ROS). This increase leads to lipid peroxidation, abnormal cellular function and cell death. Combined, the enzymatic and non-enzymatic antioxidant defense systems become deficient and there is a consequent uncontrolled generation of ROS that culminates in renal tissue damage. Still, few epidemiological and experimental studies have reported renal impact correlated to OTs exposure. This lack of investigation of the complete effect of OTs in renal function and structure led us to perform this review reporting the main researches about this subject.